2016
DOI: 10.1175/jas-d-15-0278.1
|View full text |Cite
|
Sign up to set email alerts
|

Past, Present, and Future Atmospheric Nitrogen Deposition

Abstract: Reactive nitrogen emissions into the atmosphere are increasing as a result of human activities, affecting nitrogen deposition to the surface and impacting the productivity of terrestrial and marine ecosystems. An atmospheric chemistry-transport model [Tracer Model 4 of the Environmental Chemical Processes Laboratory (TM4-ECPL)] is here used to calculate the global distribution of total nitrogen deposition, accounting for the first time for both its inorganic and organic fractions in gaseous and particulate pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
158
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 255 publications
(167 citation statements)
references
References 39 publications
8
158
0
1
Order By: Relevance
“…NO y deposition was estimated to be around 45-50 Tg N yr −1 in the late 1990s and early 2000s, representing a three-to fourfold increase since the preindustrial era (Dentener et al, 2006;Kanakidou et al, 2016;Lamarque et al, 2013). A substantial range exists in the trajectory of global NO y deposition beyond the year 2000, depending on the emission scenario.…”
Section: Introductionmentioning
confidence: 99%
“…NO y deposition was estimated to be around 45-50 Tg N yr −1 in the late 1990s and early 2000s, representing a three-to fourfold increase since the preindustrial era (Dentener et al, 2006;Kanakidou et al, 2016;Lamarque et al, 2013). A substantial range exists in the trajectory of global NO y deposition beyond the year 2000, depending on the emission scenario.…”
Section: Introductionmentioning
confidence: 99%
“…Dentener et al (2006) the Unites States is found to deviate with inferential dry deposition data. Kanakidou et al (2016) used the ACCMIP simulation results under historical, RCP6.0 and RCP 8.5 emission scenarios to 90 estimate the changes in N deposition driven by human activity in the past (1850), present (2005) and future (2050). Their results showed that organic nitrogen (ON) from primary emission and secondary organic aerosol (SOA) accounted for 20-30% of total N deposition.…”
Section: Introductionmentioning
confidence: 99%
“…This benefit is compensated by increasing NH x deposition because no limitation is implemented on NH 3 emission (Kanakidou et al, 2016;Li et al, 2016). Some regions have small increases in the ratio of NH x deposition, such as North Europe (Norway) (5%), Southeast Asia (10%) and Western Australia (10%).…”
mentioning
confidence: 99%
“…Atmospheric nitrogen deposition caused by human activities has been receiving much attention (Kanakidou et al, 2016). The annual anthropogenic input of nitrogen in ecosystems has increased tenfold over the past 150 years, and it is predicted to be 2-3 times the current level in the 2050s (Sutton and Bleeker, 2013).…”
Section: Introductionmentioning
confidence: 99%